2020
DOI: 10.22219/jk.v11i1.9752
|View full text |Cite
|
Sign up to set email alerts
|

Early Home Care Errors and the Impact on Delay in Hospital for Patients with Coronary Heart Disease

Abstract: Introduction: Heart disease is a major problem in public health lately. Delay in treatment is still a major problem in managing coronary heart disease. Objective: The purpose of this study was to analyze the pre-hospital care of a heart attack and its relationship with the delay to the hospital. Method: The study was conducted at Dr. Hardjono Ponorogo Regency, a representative sample of 108 respondents was taken purposively. The cross-sectional analytic design was conducted to measure the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This is not following the other literature review, which states that the supporting examinations are ECG, cardiac enzymes, laboratory tests, X-rays and echocardiography or cardiac ultrasound (Jakovljevic, 2018). The provision of therapy was not found to be a gap between the case review and the literature review (Rosjidi, 2020). In the case review, it was found that the therapy given was oxygen, analgesics, antibiotics, sublingual nitroglycerin and cedocard.…”
Section: Assessmentmentioning
confidence: 93%
See 1 more Smart Citation
“…This is not following the other literature review, which states that the supporting examinations are ECG, cardiac enzymes, laboratory tests, X-rays and echocardiography or cardiac ultrasound (Jakovljevic, 2018). The provision of therapy was not found to be a gap between the case review and the literature review (Rosjidi, 2020). In the case review, it was found that the therapy given was oxygen, analgesics, antibiotics, sublingual nitroglycerin and cedocard.…”
Section: Assessmentmentioning
confidence: 93%
“…The intervention provided was in accordance with the OMEK rules. And adapted to the facilities owned by the hospital (Rosjidi, 2020).…”
Section: Nursing Interventionsmentioning
confidence: 99%
“…Misperceptions about the cardiovascular disease are thought to affect alertness to cardiovascular disease (Rosjidi, 2020).…”
Section: Introductionmentioning
confidence: 99%